Greek sculpture - Spivey, Nigel Jonathan, 1958- (Cambridge)
xxii, 329 sayfa
Keywords: “Ancient Greek sculpture seems to have a timeless quality - provoking reactions that may range from awe to alienation. Yet it was a particular product of its age: and to know how and why it was once created is to embark upon an understanding of its 'Classic' status. In this richly-illustrated and carefully-written survey, encompassing works from c. 700 BC to the end of antiquity, Nigel Spivey expounds not only the social function of Greek sculpture but also its aesthetic and technical achievement. Fresh approaches are reconciled with traditional modes of study as the connoisseurship of this art is sympathetically unravelled, while source material and historical narratives are woven into detailed explanations, putting the art into its proper context.” --